Nutritional Survey of Elite Elderly Japanese Athletes - Yanagisawa, Kae; Okumoto, Tadashi; Katsuta, Shigeru; Tokuyama, Kumpei; Kikuchi, Masataka (Eiyōgaku zasshi, 2005)
Aging is a highly individualized process, resulting in large differences in health and function. The importance of physical activity for maintaining health and successful aging is gaining recognition, and an increasing number of elderly people are now engaged in recreational physical activity. Although very limited, some are involved in sports and competitive athletic events. The present study examines the nutritional status of elite elderly Japanese athletes aged between 74 and 90 years (8 females 80.4±3.6 years; 7 males 84.7±2.2 years), including four world record holders in their age category. Dietitians recorded the diets of the subjects for three consecutive days at their homes, and the nutritional contents of their diets were estimated according to the Standard Tables of Food Composition in Japan. Compared with age-matched individuals in the 2001 National Nutritional Survey of Japan (NNSJ), all nutrient intake, except for vitamin A by the females, was more than that of the sedentary individuals. Large individual differences were apparent in the intake in terms of food groups. However, the nutrient intake per 1, 000 kcal by the elderly athletes was similar to that by the age-matched individuals obtained by NNSJ. These results indicate that an enhanced energy intake enables the elderly athletes to achieve a high level of nutrient intake.